Liberalism and affirmative obligation - Smith, Patricia, 1956- (Oxford University Press, 1998)
The task before the moderate liberal is to consider what a consistently liberal view of affirmative obligation would have to be in order to accommodate liberal commitments to freedom and justice and also account for long-standing institutions that are central to liberal democratic society. In this book, Patricia Smith argues that this can be achieved by reconstructing the liberal doctrine of positive and negative duty. She offers a careful consideration of these elements of liberal principles as they relate to affirmative obligation. Through an innovative analysis of the institutions of family and contract, Smith develops the idea of duties of membership as preferable to natural duties (to explain family obligation) and as needed to supplement contractual duties (to explain professional obligation). This idea is then applied to the problem of justifying political obligation. Her discussion will interest students and scholars of legal and political philosophy and political science.